Photoacoustic measurement of thermal diffusivity of polypyrrole conducting polymer composite films - Lim, Mei Yee; Mat Yunus, Wan Mahmood; Kassim, Anuar; Mahmud, Habibun Nabi Muhammad Ekramul (Science Publications, 2009)
The thermal diffusivity has been measured for the Polypyrrole-Polyethylene Glycol (PPy-PEG) composite films by the open photoacoustic method. The experimental data were analyzed for thermal diffusivity by fitting procedure. The different process parameters such as different concentrations of insulating polymer, monomer and electrolyte and the different voltages used to prepare the PPy-PEG composite films brought changes in thermal diffusivity. The process condition of 0.20 M pyrrole, 0.10 M p-toluene sulfonate and 1×10-3 M PEG at 1.20 volt (vs SCE) appeared as the optimum condition and the PPy-PEG composite film produced from this optimum condition shows the highest thermal diffusivity (7.88×10-7 m2 s-1).